Preparation method of PDA modified PAA / LDH super-hydrophobic aluminum-based corrosion-resistant surface
Patent Information
- Application Number
- CN202311597307.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-11-27
AI Technical Summary
当前制备的超疏水表面粗糙结构和疏水改性层与基底结合力弱,机械稳定性差,表面化学组成不均匀,超疏水表面发生润湿转换的能量势垒较低,在实际抗腐蚀过程中,超疏水表面在于水及侵蚀性离子长期接触后,粗超结构中滞留空气层发生逃逸和溶解甚至粗糙结构被破坏,诱导Cassie型复合接触向Wenzel型均质接触转换,导致相应抗腐蚀性能的退化
[0026]1、本发明通过阳极氧化技术在铝基体上构建封闭、独立、有序多孔PAA结构,进而采用水热法在PAA多孔壁上原位生长LDH,构建分级粗糙结构,粗糙结构与疏水改性剂间通过PDA进行桥接,制备超疏水耐蚀表面。封闭的多孔有序结构及原位生长的LDH结构将提高超疏水表面润湿转换能量势垒和机械稳定性,而粘附力强、官能团丰富的PDA作为桥接介质提高了表面疏水层的化学稳定性和化学组成的均一性,进一步提高超疏水界面稳定性和表面抗腐蚀性能。
Smart Images

Figure CN117845215B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal surface treatment technology, specifically relating to a method for preparing a superhydrophobic and corrosion-resistant surface on aluminum and aluminum alloys. Background Technology
[0002] Low-density aluminum and aluminum alloys possess high strength, excellent mechanical properties, and good ductility, making them increasingly used as structural materials in shipbuilding and marine engineering. However, traditional corrosion protection systems for aluminum and aluminum alloys are susceptible to corrosion from water and chloride ions in marine environments. - Ion attack leads to localized corrosion such as pitting, significantly reducing the lifespan of devices and equipment, and even causing complete failure within a short period, thus limiting the application and promotion of aluminum and aluminum alloys in marine environments. The micro-nano-level rough structure of superhydrophobic surfaces traps an air layer, reducing the contact area between the liquid and solid surfaces while effectively preventing the invasion of ionized chloride ions. - Contact between ions and the metal substrate prevents corrosion. Currently prepared superhydrophobic surfaces with rough structures and hydrophobic modified layers exhibit weak adhesion to the substrate, poor mechanical stability, and uneven surface chemical composition. The energy barrier for wetting transition on superhydrophobic surfaces is low. In actual corrosion resistance processes, after prolonged contact with water and corrosive ions, the trapped air layer in the rough superhydrophobic structure escapes and dissolves, and the rough structure may even be destroyed. This induces a transformation from Cassie-type composite contacts to Wenzel-type homogeneous contacts, leading to a degradation of the corresponding corrosion resistance.
[0003] Anodizing aluminum and aluminum alloy surfaces can create independent, closed-pore structures in situ. This increases substrate adhesion while making it more difficult for trapped air to escape from the pores, thus preventing water and Cl- from escaping. - Ions contact the metal matrix, improving surface corrosion resistance. However, the air trapped within the independent pore structure gradually dissipates over time due to internal and external environmental factors. Constructing a hierarchical roughening structure within the independent pore structure to increase its roughness and improve the stability of the trapped air layer is an effective way to overcome the limitations of corrosion resistance applications on superhydrophobic surfaces of aluminum and aluminum alloys. Summary of the Invention
[0004] This invention provides a method for preparing corrosion-resistant superhydrophobic surfaces on aluminum and aluminum alloy surfaces. The hierarchical rough structure of the superhydrophobic surface prepared by this method consists of independent ordered porous alumina (PAA) structures and layered bimetallic hydroxides (LDHs) grown in situ on the pore walls. A highly adhesive polydopamine (PDA) rich in functional groups is introduced between the rough structure and the surface hydrophobic modification layer to improve the chemical stability and chemical composition uniformity of the surface hydrophobic modification layer, further enhancing the stability and corrosion resistance of the superhydrophobic surface.
[0005] The technical solution of this invention is: a method for preparing a PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface, comprising the following steps:
[0006] Step 1: Preparation of independent, closed, and ordered porous PAA surface:
[0007] First, the cut high-purity aluminum sheets were annealed in a muffle furnace at 450℃. After annealing, the surface organic solvents and oxides were removed with acetone and 1 mol / L NaOH solution. The cleaned high-purity aluminum sheets were then polished in a polishing solution with a phosphoric acid:sulfuric acid:ethylene glycol ratio of 3:1:2:4 (volume ratio). The polishing current density was 25 A / dm², the time was 15 min, and the temperature was 80℃. After polishing, the aluminum sheets were rinsed with deionized water and allowed to air dry.
[0008] The porous ordered PAA membrane was prepared using a two-stage anodizing method. First, polished aluminum sheets were placed in an oxalic acid-ethanol-water electrolyte (ethanol:water = 1:4 (v:v), oxalic acid concentration 0.3 mol / L) for a single anodizing step. Pre-oxidation was performed at 50 V for 8 min, followed by increasing the voltage to 80 V, 90 V, 100 V, and 110 V at a rate of 0.5-0.8 V / s, oxidizing for 25 min at a temperature controlled at 5℃ (ice-water bath). The anodized sample was then placed in a 65℃ solution of phosphoric acid (6 wt%) and chromic acid (1.8 wt%) for 40 min, and then rinsed thoroughly with deionized water. The cleaned sample was then placed in the electrolyte for a second anodizing step to obtain the porous ordered PAA membrane.
[0009] Step 2, Preparation of LDH / PAA hierarchical roughened surface structure:
[0010] Weigh out Zn(NO3)2·6H2O(Mg(NO3)2·6H2O) and NH4NO3 in the corresponding amounts of deionized water at a mass ratio of 1:4, stir well, and adjust the pH of the solution to 6-7 with 1% dilute ammonia. Vertically suspend the Al substrate in the LDH growth solution, sonicate to remove air bubbles from the substrate surface, react at a specific temperature for a specific time, remove the reaction substrate, wash it 6-7 times with deionized water, and dry it at 70℃ for later use.
[0011] Step 3, Preparation of PDA-modified LDH / PAA surface:
[0012] The calculated amount of tris(hydroxymethyl)aminomethane was dissolved in a certain amount of deionized water to make the concentration of tris(hydroxymethyl)aminomethane 10 mmol·L⁻¹. -1 Stir well. Add 1 mol·L⁻¹ of the well-stirred tris(hydroxymethyl)aminomethane solution dropwise. -1 The pH of the Tris buffer is obtained by adjusting the pH of the HCl to 8.5.
[0013] Dopamine hydrochloride was added to the prepared Tris buffer to achieve a concentration of 2 mg / mL. -1 Stir well to obtain the PDA modified solution.
[0014] The sample prepared in step two was placed vertically in the PDA modification solution and reacted at room temperature for 24 hours. After that, the sample was taken out, the surface layer of the sample was rinsed with deionized water, and then dried with compressed air to obtain the PDA-modified LDH / PAA surface.
[0015] Step 4, Preparation of PDA-modified LDH / PAA superhydrophobic surface:
[0016] Perfluorodecyltriethoxysilane (modified heptadecafluorodecylsilane) was dissolved in an ethanol / water mixture at a concentration of 2 wt%, wherein the ethanol:water ratio was 1:4 (m:m). The pH was adjusted to 5-7 with 45 wt% glacial acetic acid to obtain the modified heptadecafluorodecylsilane solution.
[0017] The sample prepared in step 3 was placed in a heptadecafluorodecylsilane modification solution and reacted at 40°C for 48 hours. After that, the sample was taken out, the surface layer of the sample was rinsed with deionized water, and dried at 80°C for 4 hours to obtain the PDA-modified LDH / PAA superhydrophobic surface.
[0018] The present invention discloses a method for preparing a PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface. Step one involves preparing an independent, closed, and ordered porous PAA surface; step two involves preparing an LDH / PAA hierarchical rough structure surface; step three involves preparing a PDA-modified LDH / PAA surface; and step four involves preparing a PDA-modified LDH / PAA superhydrophobic surface. Porous alumina (PAA) is constructed on the aluminum-based surface using anodizing technology, and a layered bimetallic hydroxide (LDH) hierarchical rough structure is grown in situ on the PAA pore walls to improve the wetting conversion energy barrier and mechanical stability of the superhydrophobic surface. Simultaneously, highly adhesive polydopamine (PDA), rich in functional groups, is introduced between the rough structure and the surface hydrophobic modification layer to improve the chemical stability and chemical composition uniformity of the surface hydrophobic modification layer, further enhancing the superhydrophobic interface stability and surface corrosion resistance.
[0019] Preferably, the polishing solution in step one is a phosphoric acid-sulfuric acid-ethylene glycol system.
[0020] Preferably, the electrolyte system in step one is an oxalic acid-ethanol-water system electrolyte.
[0021] Preferably, the LDH growth solution system in step two uses Zn(NO3)2·6H2O(Mg(NO3)2·6H2O) and NH4NO3.
[0022] Preferably, ammonia is used as a pH adjuster in step two.
[0023] Preferably, in step three, the concentration of PDA is [value], the reaction temperature is [value], and the reaction time is [value].
[0024] Preferably, the hydrophobic modifier in step four is perfluorodecyltriethoxysilane.
[0025] The beneficial effects of this invention are as follows:
[0026] 1. This invention constructs a closed, independent, and ordered porous PAA structure on an aluminum substrate using anodizing technology. Then, LDH is grown in situ on the porous walls of the PAA using a hydrothermal method to construct a hierarchical rough structure. The rough structure and the hydrophobic modifier are bridged by PDA, thus preparing a superhydrophobic and corrosion-resistant surface. The closed porous ordered structure and the in-situ grown LDH structure improve the wetting conversion energy barrier and mechanical stability of the superhydrophobic surface. Meanwhile, the highly adhesive and functionally rich PDA acts as a bridging medium, improving the chemical stability and chemical composition uniformity of the surface hydrophobic layer, further enhancing the stability of the superhydrophobic interface and the surface corrosion resistance.
[0027] 2. The closed, independent, and ordered porous PAA structure increases the difficulty of direct air escape from the pores, effectively preventing corrosive media from contacting the metal substrate and avoiding corrosion reactions.
[0028] 3. The LDH hierarchical rough structure grown in situ on the pore wall uses the substrate metal as the raw material source and is prepared by in situ growth. It has excellent adhesion to the substrate, and the hierarchical rough structure in the closed pore further increases the difficulty of the escape of trapped air, while increasing the wetting conversion energy barrier of the superhydrophobic surface.
[0029] 4. The PDA bridging the rough structure and the hydrophobic modifier contains abundant active functional groups such as phenolic hydroxyl and amino groups. Through chemical bonding with the hydrophobic modifier, it improves the substrate bonding force of the hydrophobic modifier and the uniformity of the chemical composition of the superhydrophobic surface, further enhancing the stability of the hydrophobic interface and the surface corrosion resistance. Attached Figure Description
[0030] Figure 1 This is a test diagram of the hydrophobic angle of the PDA-modified LDH / PAA superhydrophobic aluminum-based corrosion-resistant surface described in this invention.
[0031] Figure 2 The electrochemical impedance spectroscopy results of the PDA-modified PAA / LDH superhydrophobic aluminum-based anti-corrosion surface prepared in Example 5 were obtained using a CHI760E electrochemical workstation. Detailed Implementation
[0032] The present invention will now be described in detail with reference to the embodiments.
[0033] Example 1:
[0034] 1. Preparation of PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface
[0035] Step 1: Preparation of independent, closed, and ordered porous PAA surface:
[0036] (1) Aluminum sheet annealing: Cut aluminum foil into substrates of 5.0cm×2.0cm, place the cut substrates in a muffle furnace, heat from room temperature to 450℃ at a heating rate of 10℃ / min, hold for 4h, and cool with the furnace.
[0037] (2) Surface treatment: After annealing, the sample was ultrasonicated with acetone and ethanol for 15 min to remove the organic solvent on the surface. Then it was washed three times with deionized water and placed in 1 mol / L sodium hydroxide solution for 10 min to remove the surface oxides. After washing three times with deionized water, it was naturally dried and ready for use.
[0038] (3) Electrochemical polishing: The surface-treated sample was placed in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol: water = 3:1:2:4 (volume ratio) for polishing, with a current density of 25 A / m. 2 The time was 15 minutes and the temperature was 80℃. After the process, the sample was rinsed with deionized water and allowed to air dry.
[0039] (4) Primary anodizing: The cleaned high-purity aluminum sample was polished in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol = 3:1:2:4 (volume ratio). The polishing current density was 25 A / dm², the time was 15 min, and the temperature was 80 °C. After polishing, the aluminum sheet was cleaned with deionized water and allowed to air dry. The polished aluminum sheet was then placed in an oxalic acid-ethanol-water electrolyte system (ethanol:water = 1:4, volume ratio; oxalic acid concentration was 0.3 mol / L) for primary anodizing. The sample was first pre-oxidized at 50 V for 8 min, and then the voltage was increased to 100 V at a rate of 0.5 V / s for 25 min, while the temperature was controlled at 5 °C (ice-water bath).
[0040] (5) Removal of oxide film: The sample after one anodizing was placed in a mixture of phosphoric acid (6wt%) and chromic acid (1.8wt%) at 65℃ and rinsed with deionized water after 40 min.
[0041] (6) Secondary anodizing: Place the cleaned sample in the electrolyte and repeat the (4) anodizing process to obtain an independent, closed, ordered porous PAA membrane.
[0042] Step 2, Preparation of LDH / PAA hierarchical roughened surface structure:
[0043] (1) Preparation of LDH growth solution: Weigh 1.4875 g of Zn(NO3)2·6H2O and 1.6010 g of NH4NO3 according to the molar ratio of Zn(NO3)2·6H2O:NH4NO3 = 1:4, and dissolve them in 50 mL of deionized water. 2+ =0.1mol / L, mix thoroughly, and adjust the pH of the solution to 6.53 with 1wt% dilute ammonia.
[0044] (2) Preparation of LDH / PAA membrane: The sample prepared in step one is vertically suspended in LDH growth solution, and the air bubbles on the surface of the sample are removed by ultrasonication. The sample is reacted in a 75℃ water bath for 120 min, the reaction substrate is removed, and the sample is washed with deionized water 6 to 7 times. The sample is then dried in a 70℃ constant temperature drying oven for 24 h to obtain the LDH / PAA membrane.
[0045] Step 3, Preparation of PDA-modified LDH / PAA surface:
[0046] (1) Preparation of Tris buffer: Dissolve 0.3037 g of tris(hydroxymethyl)aminomethane in 250 mL of deionized water and stir until homogeneous to a concentration of 10 mmol / L. Add 1 mol / L HCl to the homogeneous Tris(hydroxymethyl)aminomethane solution to adjust the pH to 8.5, thus obtaining the Tris buffer.
[0047] (2) Preparation of PDA modification solution: Dissolve 0.1g of dopamine hydrochloride in 50mL of Tris buffer prepared in step (1) to make the concentration of dopamine hydrochloride 2mg / L. Adjust the pH value to 8.48 with 1mol / L HCl to obtain the PDA modification solution.
[0048] (3) Preparation of PDA-modified LDH / PAA membrane: The sample prepared in step 2 was placed vertically in the PDA modification solution and reacted at room temperature for 24 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried with compressed air to obtain the PDA-modified LDH / PAA surface.
[0049] Step 4, Preparation of PDA-modified LDH / PAA superhydrophobic surface:
[0050] (1) Preparation of heptadecafluorodecylsilane modified solution: Dissolve 0.4g of silane coupling agent heptadecafluorodecylsilane in 20g of ethanol / water mixed solution, wherein the mass fraction of ethanol is 20wt% and the concentration of silane coupling agent is 2wt%. Adjust the pH value to 5.84 with 45wt% glacial acetic acid to obtain heptadecafluorodecylsilane modified solution.
[0051] (2) Preparation of PDA-modified LDH / PAA superhydrophobic surface: The sample prepared in step 3 was placed in the heptadecafluorodecylsilane modification solution and reacted at 40°C for 48 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried at 80°C for 4 hours to obtain the PDA-modified LDH / PAA superhydrophobic surface.
[0052] 2. Testing of the anti-corrosion surface properties of PDA-modified PAA / LDH superhydrophobic aluminum-based surface
[0053] 1) Hydrophobicity test
[0054] The surface water contact angle of the PDA-modified PAA / LDH superhydrophobic aluminum-based anti-corrosion surface prepared above was tested. The surface contact angle of the coating was 163° and the hysteresis angle was 2°, exhibiting high superhydrophobicity. See the hydrophobic angle diagram below. Figure 1 .
[0055] 2) Electrochemical performance testing
[0056] The PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface prepared above was subjected to electrochemical impedance spectroscopy (EIS) testing using a CHI760E electrochemical workstation. The test frequency was 100 kHz - 0.01 Hz, the perturbation voltage was 20 mV, the reference electrode was Ag / AgCl, the counter electrode was a platinum mesh, and the test area was 1 cm². 2 The results showed that the coating had an impedance value >10 in a 3.5 wt% NaCl solution. 9 The EIS curve is almost parallel to the vertical axis, indicating excellent corrosion resistance. The impedance test values are shown in Table 1.
[0057] Example 2:
[0058] 1. Preparation of PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface
[0059] Step 1: Preparation of independent, closed, and ordered porous PAA surface:
[0060] (1) Aluminum sheet annealing: Cut aluminum foil into substrates of 5.0cm×2.0cm, place the cut substrates in a muffle furnace, heat from room temperature to 450℃ at a heating rate of 10℃ / min, hold for 4h, and cool with the furnace.
[0061] (2) Surface treatment: After annealing, the sample was ultrasonicated with acetone and ethanol for 15 min to remove the organic solvent on the surface. Then it was washed three times with deionized water and placed in 1 mol / L sodium hydroxide solution for 10 min to remove the surface oxides. After washing three times with deionized water, it was naturally dried and ready for use.
[0062] (3) Electrochemical polishing: The surface-treated sample was placed in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol: water = 3:1:2:4 (volume ratio) for polishing, with a current density of 25 A / m. 2 The time was 15 minutes and the temperature was 80℃. After the process, the sample was rinsed with deionized water and allowed to air dry.
[0063] (4) Primary anodizing: The cleaned high-purity aluminum sample was polished in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol = 3:1:2:4 (volume ratio). The polishing current density was 25 A / dm², the time was 15 min, and the temperature was 80 °C. After polishing, the aluminum sheet was cleaned with deionized water and allowed to air dry. The polished aluminum sheet was then placed in an oxalic acid-ethanol-water electrolyte system (ethanol:water = 1:4, volume ratio; oxalic acid concentration was 0.3 mol / L) for primary anodizing. The sample was first pre-oxidized at 50 V for 8 min, and then the voltage was increased to 100 V at a rate of 0.5 V / s for 25 min, while the temperature was controlled at 5 °C (ice-water bath).
[0064] (5) Removal of oxide film: The sample after one anodizing was placed in a mixture of phosphoric acid (6wt%) and chromic acid (1.8wt%) at 65℃ and rinsed with deionized water after 40 min.
[0065] (6) Secondary anodizing: Place the cleaned sample in the electrolyte and repeat the (4) anodizing process to obtain an independent, closed, ordered porous PAA membrane.
[0066] Step 2, Preparation of LDH / PAA hierarchical roughened surface structure:
[0067] (1) Preparation of LDH growth solution: Weigh 1.2820 g of Mg(NO3)2·6H2O and 1.6010 g of NH4NO3 according to the molar ratio of Mg(NO3)2·6H2O:NH4NO3 = 1:4, and dissolve them in 50 mL of deionized water. 2+ =0.1mol / L, mix thoroughly, and adjust the pH of the solution to 6.57 with 1wt% dilute ammonia.
[0068] (2) Preparation of LDH / PAA membrane: The sample prepared in step one is vertically suspended in LDH growth solution, and the air bubbles on the surface of the sample are removed by ultrasonication. The sample is reacted in a 75℃ water bath for 120 min, the reaction substrate is removed, and the sample is washed with deionized water 6 to 7 times. The sample is then dried in a 70℃ constant temperature drying oven for 24 h to obtain the LDH / PAA membrane.
[0069] Step 3, Preparation of PDA-modified LDH / PAA surface:
[0070] (1) Preparation of Tris buffer: Dissolve 0.3037 g of tris(hydroxymethyl)aminomethane in 250 mL of deionized water and stir until homogeneous to a concentration of 10 mmol / L. Add 1 mol / L HCl to the homogeneous Tris(hydroxymethyl)aminomethane solution to adjust the pH to 8.5, thus obtaining the Tris buffer.
[0071] (2) Preparation of PDA modification solution: Dissolve 0.1g of dopamine hydrochloride in 50mL of Tris buffer prepared in step (1) to make the concentration of dopamine hydrochloride 2mg / L. Adjust the pH value to 8.48 with 1mol / L HCl to obtain the PDA modification solution.
[0072] (3) Preparation of PDA-modified LDH / PAA membrane: The sample prepared in step 2 was placed vertically in the PDA modification solution and reacted at room temperature for 24 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried with compressed air to obtain the PDA-modified LDH / PAA surface.
[0073] Step 4, Preparation of PDA-modified LDH / PAA superhydrophobic surface:
[0074] (1) Preparation of heptadecafluorodecylsilane modified solution: Dissolve 0.4g of silane coupling agent heptadecafluorodecylsilane in 20g of ethanol / water mixed solution, wherein the mass fraction of ethanol is 20wt% and the concentration of silane coupling agent is 2wt%. Adjust the pH value to 5.84 with 45wt% glacial acetic acid to obtain heptadecafluorodecylsilane modified solution.
[0075] (2) Preparation of PDA-modified LDH / PAA superhydrophobic surface: The sample prepared in step 3 was placed in the heptadecafluorodecylsilane modification solution and reacted at 40°C for 48 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried at 80°C for 4 hours to obtain the PDA-modified LDH / PAA superhydrophobic surface.
[0076] 2. Testing of the anti-corrosion surface properties of PDA-modified PAA / LDH superhydrophobic aluminum-based surface
[0077] 1) Hydrophobicity test
[0078] The PDA-modified PAA / LDH superhydrophobic aluminum-based anti-corrosion surface prepared above was tested for surface water contact angle. The surface contact angle of the coating was 158° and the hysteresis angle was 4°, which showed high superhydrophobicity.
[0079] The PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface prepared above was subjected to electrochemical impedance spectroscopy (EIS) testing using a CHI760E electrochemical workstation. The test frequency was 100 kHz - 0.01 Hz, the perturbation voltage was 20 mV, the reference electrode was Ag / AgCl, the counter electrode was a platinum mesh, and the test area was 1 cm².2 The results showed that the coating had an impedance value >10 in a 3.5 wt% NaCl solution. 9 The impedance is on the order of magnitude, indicating that the superhydrophobic film has a very high impedance value and exhibits excellent corrosion resistance. The impedance test values are shown in Table 1.
[0080] Example 3:
[0081] 1. Preparation of PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface
[0082] Step 1: Preparation of independent, closed, and ordered porous PAA surface:
[0083] (1) Aluminum sheet annealing: Cut aluminum foil into substrates of 5.0cm×2.0cm, place the cut substrates in a muffle furnace, heat from room temperature to 450℃ at a heating rate of 10℃ / min, hold for 4h, and cool with the furnace.
[0084] (2) Surface treatment: After annealing, the sample was ultrasonicated with acetone and ethanol for 15 min to remove the organic solvent on the surface. Then it was washed three times with deionized water and placed in 1 mol / L sodium hydroxide solution for 10 min to remove the surface oxides. After washing three times with deionized water, it was naturally dried and ready for use.
[0085] (3) Electrochemical polishing: The surface-treated sample was placed in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol: water = 3:1:2:4 (volume ratio) for polishing, with a current density of 25 A / m. 2 The time was 15 minutes and the temperature was 80℃. After the process, the sample was rinsed with deionized water and allowed to air dry.
[0086] (4) Primary anodizing: The cleaned high-purity aluminum sample was placed in a polishing solution with a volume ratio of 85% phosphoric acid, 98% sulfuric acid, and ethylene glycol of 3:1:2:4. The polishing current density was 25 A / dm³. 2 The process was carried out for 15 minutes at 80℃. After polishing, the aluminum sheet was cleaned with deionized water and allowed to air dry. The polished aluminum sheet was then placed in an oxalic acid-ethanol-water electrolyte (ethanol:water = 1:4, volume ratio; oxalic acid concentration 0.3mol / L) for a single anodizing. The sample was first pre-oxidized at 50V for 8 minutes, then the voltage was increased to 80V at a rate of 0.5V / s for 25 minutes, with the temperature controlled at 5℃ (ice-water bath).
[0087] (5) Removal of oxide film: The sample after one anodizing was placed in a mixture of phosphoric acid (6wt%) and chromic acid (1.8wt%) at 65℃ and rinsed with deionized water after 40 min.
[0088] (6) Secondary anodizing: Place the cleaned sample in the electrolyte and repeat the (4) anodizing process to obtain an independent, closed, ordered porous PAA membrane.
[0089] Step 2, Preparation of LDH / PAA hierarchical roughened surface structure:
[0090] (1) Preparation of LDH growth solution: Weigh 1.4875 g of Zn(NO3)2·6H2O and 1.6010 g of NH4NO3 according to the molar ratio of Zn(NO3)2·6H2O:NH4NO3 = 1:4, dissolve them in 50 mL of deionized water, c(Mg 2+ =0.1mol / L, mix thoroughly, and adjust the pH of the solution to 6.55 with 1wt% dilute ammonia.
[0091] (2) Preparation of LDH / PAA membrane: The sample prepared in step one is vertically suspended in LDH growth solution, and the air bubbles on the surface of the sample are removed by ultrasonication. The sample is reacted in a 75℃ water bath for 120 min, the reaction substrate is removed, and the sample is washed with deionized water 6 to 7 times. The sample is then dried in a 70℃ constant temperature drying oven for 24 h to obtain the LDH / PAA membrane.
[0092] Step 3, Preparation of PDA-modified LDH / PAA surface:
[0093] (1) Preparation of Tris buffer: Dissolve 0.3037 g of tris(hydroxymethyl)aminomethane in 250 mL of deionized water and stir until homogeneous to a concentration of 10 mmol / L. Add 1 mol / L HCl to the homogeneous Tris(hydroxymethyl)aminomethane solution to adjust the pH to 8.5, thus obtaining the Tris buffer.
[0094] (2) Preparation of PDA modification solution: Dissolve 0.1g of dopamine hydrochloride in 50mL of Tris buffer prepared in step (1) to make the concentration of dopamine hydrochloride 2mg / L. Adjust the pH value to 8.48 with 1mol / L HCl to obtain the PDA modification solution.
[0095] (3) Preparation of PDA-modified LDH / PAA membrane: The sample prepared in step 2 was placed vertically in the PDA modification solution and reacted at room temperature for 24 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried with compressed air to obtain the PDA-modified LDH / PAA surface.
[0096] Step 4, Preparation of PDA-modified LDH / PAA superhydrophobic surface:
[0097] (1) Preparation of heptadecafluorodecylsilane modified solution: Dissolve 0.4g of silane coupling agent heptadecafluorodecylsilane in 20g of ethanol / water mixed solution, wherein the mass fraction of ethanol is 20wt% and the concentration of silane coupling agent is 2wt%. Adjust the pH value to 5.84 with 45wt% glacial acetic acid to obtain heptadecafluorodecylsilane modified solution.
[0098] (2) Preparation of PDA-modified LDH / PAA superhydrophobic surface: The sample prepared in step 3 was placed in the heptadecafluorodecylsilane modification solution and reacted at 40°C for 48 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried at 80°C for 4 hours to obtain the PDA-modified LDH / PAA superhydrophobic surface.
[0099] 2. Testing of the anti-corrosion surface properties of PDA-modified PAA / LDH superhydrophobic aluminum-based surface
[0100] 1) Hydrophobicity test
[0101] The PDA-modified PAA / LDH superhydrophobic aluminum-based anti-corrosion surface prepared above was tested for surface water contact angle. The surface contact angle of the coating was 151° and the hysteresis angle was 7°, which showed high superhydrophobicity.
[0102] 2) Electrochemical performance testing
[0103] The PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface prepared above was subjected to electrochemical impedance spectroscopy (EIS) testing using a CHI760E electrochemical workstation. The test frequency was 100 kHz - 0.01 Hz, the perturbation voltage was 20 mV, the reference electrode was Ag / AgCl, the counter electrode was a platinum mesh, and the test area was 1 cm². 2 The results showed that the coating had an impedance value >10 in a 3.5 wt% NaCl solution. 9 The impedance is on the order of magnitude, indicating that the superhydrophobic film has a very high impedance value and exhibits excellent corrosion resistance. The impedance test values are shown in Table 1.
[0104] Example 4:
[0105] 1. Preparation of PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface
[0106] Step 1: Preparation of independent, closed, and ordered porous PAA surface:
[0107] (1) Aluminum sheet annealing: Cut aluminum foil into substrates of 5.0cm×2.0cm, place the cut substrates in a muffle furnace, heat from room temperature to 450℃ at a heating rate of 10℃ / min, hold for 4h, and cool with the furnace.
[0108] (2) Surface treatment: After annealing, the sample was ultrasonicated with acetone and ethanol for 15 min to remove the organic solvent on the surface. Then it was washed three times with deionized water and placed in 1 mol / L sodium hydroxide solution for 10 min to remove the surface oxides. After washing three times with deionized water, it was naturally dried and ready for use.
[0109] (3) Electrochemical polishing: The surface-treated sample was placed in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol: water = 3:1:2:4 (volume ratio) for polishing, with a current density of 25 A / m. 2 The time was 15 minutes and the temperature was 80℃. After the process, the sample was rinsed with deionized water and allowed to air dry.
[0110] (4) Primary anodizing: The cleaned high-purity aluminum sample was polished in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol = 3:1:2:4 (volume ratio). The polishing current density was 25 A / dm², the time was 15 min, and the temperature was 80 °C. After polishing, the aluminum sheet was cleaned with deionized water and allowed to air dry. The polished aluminum sheet was then placed in an oxalic acid-ethanol-water electrolyte system (ethanol:water = 1:4, volume ratio; oxalic acid concentration was 0.3 mol / L) for primary anodizing. The sample was first pre-oxidized at 50 V for 8 min, and then the voltage was increased to 100 V at a rate of 0.5 V / s for 25 min, while the temperature was controlled at 5 °C (ice-water bath).
[0111] (5) Removal of oxide film: The sample after one anodizing was placed in a mixture of phosphoric acid (6wt%) and chromic acid (1.8wt%) at 65℃ and rinsed with deionized water after 40 min.
[0112] (6) Secondary anodizing: Place the cleaned sample in the electrolyte and repeat the (4) anodizing process to obtain an independent, closed, ordered porous PAA membrane.
[0113] Step 2, Preparation of LDH / PAA hierarchical roughened surface structure:
[0114] (1) Preparation of LDH growth solution: Weigh 1.4875 g of Zn(NO3)2·6H2O and 1.6010 g of NH4NO3 according to the molar ratio of Zn(NO3)2·6H2O:NH4NO3 = 1:4, and dissolve them in 50 mL of deionized water. 2+ =0.1mol / L, mix thoroughly, and adjust the pH of the solution to 6.53 with 1wt% dilute ammonia.
[0115] (2) Preparation of LDH / PAA membrane: The sample prepared in step one is vertically suspended in LDH growth solution, and the air bubbles on the surface of the sample are removed by ultrasonication. The sample is reacted in a 75℃ water bath for 120 min, the reaction substrate is removed, and the sample is washed with deionized water 6 to 7 times. The sample is then dried in a 70℃ constant temperature drying oven for 24 h to obtain the LDH / PAA membrane.
[0116] Step 3, Preparation of PDA-modified LDH / PAA surface:
[0117] (1) Preparation of Tris buffer: Dissolve 0.3037 g of tris(hydroxymethyl)aminomethane in 250 mL of deionized water and stir until homogeneous to a concentration of 10 mmol / L. Add 1 mol / L HCl to the homogeneous Tris(hydroxymethyl)aminomethane solution to adjust the pH to 8.5, thus obtaining the Tris buffer.
[0118] (2) Preparation of PDA modification solution: Dissolve 0.1g of dopamine hydrochloride in 50mL of Tris buffer prepared in step (1) to make the concentration of dopamine hydrochloride 2mg / L. Adjust the pH value to 8.48 with 1mol / L HCl to obtain the PDA modification solution.
[0119] (3) Preparation of PDA-modified LDH / PAA membrane: The sample prepared in step 2 was placed vertically in the PDA modification solution and reacted at room temperature for 24 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried with compressed air to obtain the PDA-modified LDH / PAA surface.
[0120] Step 4, Preparation of PDA-modified LDH / PAA superhydrophobic surface:
[0121] (1) Preparation of the modified solution of tridecafluorooctylsilane: Dissolve 0.4g of silane coupling agent heptadecafluorodecylsilane in 20g of ethanol / water mixed solution, wherein the mass fraction of ethanol is 20wt% and the concentration of silane coupling agent is 2wt%. Adjust the pH value to 5.84 with 45wt% glacial acetic acid to obtain the modified solution of heptadecafluorodecylsilane.
[0122] (2) Preparation of PDA-modified LDH / PAA superhydrophobic surface: The sample prepared in step 3 was placed in the heptadecafluorodecylsilane modification solution and reacted at 40°C for 48 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried at 80°C for 4 hours to obtain the PDA-modified LDH / PAA superhydrophobic surface.
[0123] 2. Testing of the anti-corrosion surface properties of PDA-modified PAA / LDH superhydrophobic aluminum-based surface
[0124] 1) Hydrophobicity test
[0125] The PDA-modified PAA / LDH superhydrophobic aluminum-based anti-corrosion surface prepared above was tested for surface water contact angle. The surface contact angle of the coating was 151° and the hysteresis angle was 7°, which showed high superhydrophobicity.
[0126] 2) Electrochemical performance testing
[0127] The PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface prepared above was subjected to electrochemical impedance spectroscopy (EIS) testing using a CHI760E electrochemical workstation. The test frequency was 100 kHz - 0.01 Hz, the perturbation voltage was 20 mV, the reference electrode was Ag / AgCl, the counter electrode was a platinum mesh, and the test area was 1 cm². 2 The results showed that the coating had an impedance value >10 in a 3.5 wt% NaCl solution. 9 The impedance is on the order of magnitude, indicating that the superhydrophobic film has a very high impedance value and exhibits excellent corrosion resistance. The impedance test values are shown in Table 1.
[0128] Example 5:
[0129] 1. Preparation of PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface
[0130] Step 1: Preparation of independent, closed, and ordered porous PAA surface:
[0131] (1) Aluminum sheet annealing: Cut aluminum foil into substrates of 5.0cm×2.0cm, place the cut substrates in a muffle furnace, heat from room temperature to 450℃ at a heating rate of 10℃ / min, hold for 4h, and cool with the furnace.
[0132] (2) Surface treatment: After annealing, the sample was ultrasonicated with acetone and ethanol for 15 min to remove the organic solvent on the surface. Then it was washed three times with deionized water and placed in 1 mol / L sodium hydroxide solution for 10 min to remove the surface oxides. After washing three times with deionized water, it was naturally dried and ready for use.
[0133] (3) Electrochemical polishing: The surface-treated sample was placed in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol: water = 3:1:2:4 (volume ratio) for polishing, with a current density of 25 A / m. 2 The time was 15 minutes and the temperature was 80℃. After the process, the sample was rinsed with deionized water and allowed to air dry.
[0134] (4) Primary anodizing: The cleaned high-purity aluminum sample was polished in a polishing solution of phosphoric acid (85%): sulfuric acid (98%): ethylene glycol = 3:1:2:4 (volume ratio). The polishing current density was 25 A / dm², the time was 15 min, and the temperature was 80 °C. After polishing, the aluminum sheet was cleaned with deionized water and allowed to air dry. The polished aluminum sheet was then placed in an oxalic acid-ethanol-water electrolyte system (ethanol:water = 1:4, volume ratio; oxalic acid concentration was 0.3 mol / L) for primary anodizing. The sample was first pre-oxidized at 50 V for 8 min, and then the voltage was increased to 100 V at a rate of 0.5 V / s for 25 min, while the temperature was controlled at 5 °C (ice-water bath).
[0135] (5) Removal of oxide film: The sample after one anodizing was placed in a mixture of phosphoric acid (6wt%) and chromic acid (1.8wt%) at 65℃ and rinsed with deionized water after 40 min.
[0136] (6) Secondary anodizing: Place the cleaned sample in the electrolyte and repeat the (4) anodizing process to obtain an independent, closed, ordered porous PAA membrane.
[0137] Step 2, Preparation of LDH / PAA hierarchical roughened surface structure:
[0138] (1) Preparation of LDH growth solution: Weigh 1.4875 g of Zn(NO3)2·6H2O and 1.6010 g of NH4NO3 according to the molar ratio of Zn(NO3)2·6H2O:NH4NO3 = 1:4, and dissolve them in 50 mL of deionized water. 2+ =0.1mol / L, mix thoroughly, and adjust the pH of the solution to 6.53 with 1wt% dilute ammonia.
[0139] (2) Preparation of LDH / PAA membrane: The sample prepared in step one is vertically suspended in LDH growth solution, and the air bubbles on the surface of the sample are removed by ultrasonication. The sample is reacted in a 75℃ water bath for 120 min, the reaction substrate is removed, and the sample is washed with deionized water 6 to 7 times. The sample is then dried in a 70℃ constant temperature drying oven for 24 h to obtain the LDH / PAA membrane.
[0140] Step 3, Preparation of PDA-modified LDH / PAA surface:
[0141] (1) Preparation of Tris buffer: Dissolve 0.3037 g of tris(hydroxymethyl)aminomethane in 250 mL of deionized water and stir until homogeneous to a concentration of 10 mmol / L. Add 1 mol / L HCl to the homogeneous Tris(hydroxymethyl)aminomethane solution to adjust the pH to 8.5, thus obtaining the Tris buffer.
[0142] (2) Preparation of PDA modification solution: Dissolve 0.1g of dopamine hydrochloride in 50mL of Tris buffer prepared in step (1) to make the concentration of dopamine hydrochloride 2mg / L. Adjust the pH value to 8.48 with 1mol / L HCl to obtain the PDA modification solution.
[0143] (3) Preparation of PDA-modified LDH / PAA membrane: The sample prepared in step 2 was placed vertically in the PDA modification solution and reacted at room temperature for 24 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried with compressed air to obtain the PDA-modified LDH / PAA surface.
[0144] Step 4, Preparation of PDA-modified LDH / PAA superhydrophobic surface:
[0145] (1) Preparation of heptadecafluorodecylsilane modified solution: 0.8g of silane coupling agent heptadecafluorodecylsilane was dissolved in 19.2g of ethanol / water mixed solution, wherein the mass fraction of ethanol was 20wt% and the concentration of silane coupling agent was 4wt%. The pH value was adjusted to 5.84 with 45wt% glacial acetic acid to obtain heptadecafluorodecylsilane modified solution.
[0146] (2) Preparation of PDA-modified LDH / PAA superhydrophobic surface: The sample prepared in step 3 was placed in the heptadecafluorodecylsilane modification solution and reacted at 40°C for 48 hours. After taking it out, the surface layer of the sample was rinsed with deionized water and dried at 80°C for 4 hours to obtain the PDA-modified LDH / PAA superhydrophobic surface.
[0147] 2. Testing of the anti-corrosion surface properties of PDA-modified PAA / LDH superhydrophobic aluminum-based surface
[0148] 1) Hydrophobicity test
[0149] The PDA-modified PAA / LDH superhydrophobic aluminum-based anti-corrosion surface prepared above was tested for surface water contact angle. The surface contact angle of the coating was 160° and the hysteresis angle was 5°, which showed high superhydrophobicity.
[0150] 2) Electrochemical performance testing
[0151] Combination Figure 2 The test frequency was 100kHz-0.01Hz, the perturbation voltage was 20mV, the reference electrode was Ag / AgCl, the counter electrode was a platinum mesh, and the test area was 1cm². 2 The results showed that the coating had an impedance value >10 in a 3.5 wt% NaCl solution. 9 The impedance is on the order of magnitude, indicating that the superhydrophobic film has a very high impedance value, exhibiting excellent corrosion resistance. Impedance test values can be found in [reference needed]. Figure 2 .
[0152]
[0153] Table 1
[0154] The results above show that the PDA-modified PAA / LDH superhydrophobic aluminum-based anti-corrosion surface prepared by the method of the present invention has high hydrophobicity and good anti-corrosion performance.
[0155] It should be noted that the descriptions of these embodiments are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. In addition, the above are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
Claims
1. A method for preparing a PDA-modified PAA / LDH superhydrophobic aluminum-based corrosion-resistant surface, characterized in that, Includes the following steps: Step 1: Preparation of a closed, ordered, porous PAA surface: First, the cut high-purity aluminum was placed in a muffle furnace and annealed at 450℃. After annealing, the high-purity aluminum sheets were cleaned with acetone and 1 mol / L NaOH solution to remove surface organic solvents and oxides. The cleaned high-purity aluminum sheets were then polished in a polishing solution with a volume ratio of phosphoric acid:sulfuric acid:ethylene glycol:water = 3:1:2:
4. The polishing current density was 25 A / dm2, the time was 15 min, and the temperature was 80℃. After polishing, the aluminum sheets were cleaned with deionized water and allowed to air dry. The porous ordered PAA membrane was prepared by a two-stage anodizing method. First, the polished aluminum sheet was placed in an oxalic acid-ethanol-water electrolyte system with an ethanol:water volume ratio of 1:4 and an oxalic acid concentration of 0.3 mol / L for a first anodizing. The pre-oxidation was carried out at 50 V for 8 min, and then the voltage was increased to 80 V, 90 V, 100 V or 110 V at a rate of 0.5-0.8 V / s for 25 min, while the temperature was controlled at 5℃. Then, the sample after the first anodizing was placed in a 6 wt% phosphoric acid-1.8 wt% chromic acid mixture at 65℃ for 40 min, and then rinsed with deionized water. The cleaned sample was then placed in the electrolyte and the anodizing process was repeated to obtain the porous ordered PAA membrane. Step 2, Preparation of LDH / PAA hierarchical roughened surface structure: Weigh out Zn(NO3)2·6H2O or Mg(NO3)2·6H2O and NH4NO3 into the corresponding deionized water at a mass ratio of 1:4, stir evenly, and adjust the pH of the solution to 6-7 with 1% dilute ammonia. Vertically suspend the Al sheet coated with a porous ordered PAA membrane in the LDH growth solution, remove air bubbles from the substrate surface by ultrasonication, react at a certain temperature for a certain time, remove the reaction substrate, wash it with deionized water 6-7 times, and dry it at 70℃ for later use. Step 3, PDA modification of LDH / PAA surface: The calculated amount of tris(hydroxymethyl)aminomethane was dissolved in a certain amount of deionized water to make the concentration of tris(hydroxymethyl)aminomethane 10 mmol / L. The solution was stirred until homogeneous. Then, 1 mol / L HCl was added dropwise to the homogeneous tris(hydroxymethyl)aminomethane solution to adjust the pH to 8.5, thus obtaining the Tris buffer solution. Dopamine hydrochloride was added to the prepared Tris buffer solution to make the concentration of dopamine hydrochloride 2 mg / mL, and stirred evenly to obtain the PDA modified solution. The sample prepared in step two was placed vertically in the PDA modification solution and reacted at room temperature for 24 h. After that, the sample was taken out, the surface layer of the sample was rinsed with deionized water, and dried with compressed air to obtain the PDA-modified LDH / PAA surface. Step 4, Preparation of PDA-modified LDH / PAA superhydrophobic surface: Perfluorodecyltriethoxysilane was dissolved in an ethanol / water mixture at a concentration of 2 wt%, wherein the ethanol:water mass ratio was 1:
4. The pH was adjusted to 5-7 with 45 wt% glacial acetic acid to obtain a heptadecafluorodecylsilane modified solution. The sample prepared in step three was placed in the heptadecafluorodecylsilane modified solution and reacted at 40℃ for 48 h. After removal, the surface layer of the sample was rinsed with deionized water and dried at 80℃ for 4 h to obtain the PDA-modified LDH / PAA superhydrophobic surface.
Citation Information
Patent Citations
Bionic super-hydrophobic wood and preparation method thereof
CN112045808A
Preparation method and application of modified anti-corrosion super-hydrophobic integrated coating
CN112300697A